2001
DOI: 10.2105/ajph.91.6.927
|View full text |Cite
|
Sign up to set email alerts
|

The impact of homophobia, poverty, and racism on the mental health of gay and bisexual Latino men: findings from 3 US cities

Abstract: OBJECTIVES: This study assessed the relation between experiences of social discrimination (homophobia, racism, and financial hardship) and symptoms of psychologic distress (anxiety, depression, and suicidal ideation) among self-identified gay and bisexual Latino men in the United States. METHODS: Data were collected from a probability sample of 912 men (self-identified as both Latino and nonheterosexual) recruited from the venues and public social spaces identified as both Latino and gay in the cities of Miami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
286
2
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 845 publications
(335 citation statements)
references
References 7 publications
23
286
2
3
Order By: Relevance
“…Exposure to and experiences of homophobia have been implicated in substance abuse, sexual risk behaviours, negative body image, suicide attempts, increased stress and limited social support among MSM (Halkitis, Fischgrund, & Parsons, 2005;Mayer et al, 2008;Wolitski, Stall, & Valdiserri, 2008). Moreover, experiences with homophobia have been shown to interfere with the ability of MSM to establish and maintain long-term relationships, which protect against HIV acquisition (Diaz, Ayala, Bein, Henne, & Marin, 2001). The experiences of homophobia may exert their effects on sexual risk-taking indirectly by exacerbating the mental health burden (Johnson, Carrico, Chesney, & Morin, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Exposure to and experiences of homophobia have been implicated in substance abuse, sexual risk behaviours, negative body image, suicide attempts, increased stress and limited social support among MSM (Halkitis, Fischgrund, & Parsons, 2005;Mayer et al, 2008;Wolitski, Stall, & Valdiserri, 2008). Moreover, experiences with homophobia have been shown to interfere with the ability of MSM to establish and maintain long-term relationships, which protect against HIV acquisition (Diaz, Ayala, Bein, Henne, & Marin, 2001). The experiences of homophobia may exert their effects on sexual risk-taking indirectly by exacerbating the mental health burden (Johnson, Carrico, Chesney, & Morin, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…They have found that, even with a move to "symbolic" forms of discrimination (Sears 1988), the bodies and minds of racial minorities and low-income people suffer negative effects (Clark et al 1999;Landrine and Klonoff 1996;Utsey and Payne 2000;Díaz et al 2001). The effects of discrimination are even more marked when those subjects actually perceive the discrimination (Pascoe and Smart Richman 2009).…”
Section: Conclusion: Toward a Theory Of Spatial Polarization And Percmentioning
confidence: 99%
“…Sexual stigma was assessed using the Homophobia Scale, 25 adapted and validated for LBQ women. 26 Sexual stigma subscales had acceptable reliability: perceived sexual stigma (Cronbach's α = 0.70) and enacted sexual stigma (Cronbach's α = 0.73).…”
Section: Social/structural Factorsmentioning
confidence: 99%